Rhodium(I)-Catalyzed CO-Gas-Free Arylative Dual-Carbonylation of Alkynes with Arylboronic Acids via the Formyl C–H Activation of Formaldehyde - Morimoto, Tsumoru; Wang, Chuang; Tanimoto, Hiroki; Artok, Levent; Kakiuchi, Kiyomi (Synthesis, 2021)
The rhodium(I)-catalyzed reaction of alkynes with arylboronic acids in the presence of formaldehyde results in a CO-gas-free arylative dual-carbonylation to produce γ-butenolide derivatives. The simultaneous loading of phosphine-ligated and phosphine-free rhodium(I) complexes is required for efficient catalysis. The former complex catalyzes the abstraction of a carbonyl moiety from formaldehyde through the activation of its formyl C–H bond (decarbonylation) and the latter catalyzes the subsequent dual-incorporation of the resulting carbonyl unit (carbonylation). The use of larger amounts of the phosphine-ligated rhodium(I) complex generates more carbonyl units, leading to the formation γ-butenolides via the dual-incorporation of the carbonyl unit.
Keywords: C–H activation; decarbonylation; rhodium; formaldehyde; γ-butenolides; alkynes; arylboronic acids